Self-assembled fibrillar polyethylene crystals with tunable properties - (:unkn) unknown (John Wiley and Sons Inc, 2020)
Due to its simple linear chain structure, crystal morphology of linear low-density polyethylene (LLDPE) fibers can be controlled to fulfill the needs of diverse advanced applications. This study presents a simple two-step method to produce LLDPE fibers with self-assembled fibrillar crystals and highly oriented amorphous phase. Rather than conventional melt spinning, fibers were treated in a two-step eco-friendly bath without drawing after extruded fibers emerge from the spinneret. Treated fibers through the baths demonstrated lower crystallinity, but significantly higher degree of crystal orientation when compared to control fibers of traditional melt spinning. Morphological analysis revealed that a unique microstructure was formed after spinning through a two-step eco-friendly bath. As-spun fibers demonstrated spherulitic morphology which can be transformed into a fibrillar structure followed by post-drawing process. Cross sectional images of the treated LLDPE fibers produced at 400 m/min showed fibrillar PE crystals which can be more dominant upon post-drawing. After two-step bath treatment, produced fibers need low draw ratios to exhibit high performance. Our novel modification followed by hot drawing process can manipulate internal structure with performance of PE fibers to an outstanding level of 0.35 GPa strength and 3 GPa modulus at a production speed of 400 m/min. © 2020 Society of Plastics Engineers
Keywords: crystallization; high performance; polyethylene (PE); self-assembly; tunable properties